MENINGKATKAN KEMAMPUAN MENGENAL BENTUK GEOMETRI MENGGUNAKAN MEDIA PUZZLE PADA ANAK USIA DINI DI TK NEGERI 1 PEMBINA SAMARINDA - Jumiati Jumiati (JECIES: Journal of Early Childhood Islamic Education Study, 2021)
The research was distributed by the importance of the ability to know the geometric shapes in learning in early childhood education. In a study in the OLD media, which used to use a simple media using paper and haven't been able to develop the ability to know the child in geometric shapes. This is shown by an indicator of the ability to know the geometric shapes are still low. To overcome this, the researchers select and use puzzle media didasari up studies of the literature that has been done. Formulation of the problem in this study generally lifting how the ability of teachers in designing a plan of learning through media puzzle and the ability of teachers in implementing the learning through media puzzle, increased ability to know the child in the form of geometry through the media puzzle. Whereas the aim of this research is generally to describe the ability of teachers in designing rencna learning through media puzzle and describes the ability of teachers in implementing the learning through media puzzle, increases the ability to know the child in the form of geometry through the media puzzle. The methods used in this research is a Research Collaborative Class Actions with the desian and research of Kemmis Taggard. The subject of this research is the child group B2 TK Negeri 1 Pembina Samarinda City. Data collection techniques used are interviews, observation and documentation. The analysis of quantitative data using percentage and qualitative data using the Notes field. Based on the data obtained and the results of the analysis, it was concluded that the ability of teachers in designing plans and carry out learning the result very good, there is a progression of any action until I cycle cycle III. The ability to know the shape of the geometry by using the media puzzle better than each cycle I until the cycle III, compared with using media paper.